Infrastructural inequality: exploring the emergence of digital classes in the Metropolitan Area of Santiago - Correa, Juan; Ulloa León, Felipe.; Vergara Perucich, José Francisco.; Aguirre Núñez, Carlos.; Truffello, Ricardo (Nicolaus Copernicus University, 2023)
This paper examines the digital divide in the city of Santiago, Chile. The research uses the density of mobile phone antennas as a proxy for digital infrastructure. The findings show that there is a strong correlation between the density of mobile phone antennas and socioeconomic status. Areas with higher incomes and more mobile phone antennas have better Internet connectivity than areas with lower incomes and fewer mobile phone antennas. The objective is to shed light on the power dynamics and invisible networks that shape the configuration of infrastructures, highlighting the need for equitable access to the digital world as a fundamental democratic right. The conclusions indicate that communication infrastructures are unevenly distributed and that the transition from analogue to smart cities risks exacerbating social inequalities. Rectifying these disparities is essential to avoid leaving the most vulnerable behind in technological transitions.
Keywords: Chile; Clustering & digita - Segregación; Ciudades inteligentes; Ciudades y pueblos - Enseñanza